Macroeconomic Determinants of Islamic Banking Financing - Tita Nursyamsiah (Institute for Research and Community Empowerment (LPPM TAZKIA), 2017)
The purpose of this study is to analyze the relationship between Islamic banking financing and macroeconomic variables as well as its response to key economic variables including real output, price level, interest rate and trade for the case of Indonesia. This research uses time series econometric analysis such as Granger Causality and Vector Error Correction Model (VECM). Time series data used are total Islamic banking financing, industrial production index (IPI), customer price index (CPI), Certificate Bank Indonesia (SBI) rate and international trade. The results show that there is bi-directional relationship between Islamic banking financing and price level as well as Islamic banking financing and interest rate. Meanwhile, the uni directional causality occurs between Islamic banking financing and real output as well as Islamic banking financing and trade. In this case, Islamic banking financing is affected by IPI. Islamic banking financing is not affected by trade but trade is significantly affected by Islamic banking financing. In addition, Islamic banking financing is relatively sensitive to the shock of price level, real output and interest rate.